Cost‐effectiveness of hepatitis C treatment for patients in early stages of liver disease. Issue 6 (16th March 2015) - Leidner, Andrew J.; Chesson, Harrell W.; Xu, Fujie; Ward, John W.; Spradling, Philip R.; Holmberg, Scott D.
<x xml:space="preserve">Abstract</x> New treatments for hepatitis C virus (HCV) may be highly effective but are associated with substantial costs that may compel clinicians and patients to consider delaying treatment. This study investigated the cost‐effectiveness of these treatments with a focus on patients in early stages of liver disease. We developed a state‐transition (or Markov) model to calculate costs incurred and quality‐adjusted life‐years (QALYs) gained following HCV treatment, and we computed incremental cost‐effectiveness ratios (cost per QALY gained, in 2012 US dollars) for treatment at different stages of liver disease versus delaying treatment until the subsequent liver disease stage. Our analysis did not include the potential treatment benefits associated with reduced non–liver‐related mortality or preventing HCV transmission. All parameter values, particularly treatment cost, were varied in sensitivity analyses. The base case scenario represented a 55‐year‐old patient with genotype 1 HCV infection with a treatment cost of $100, 000 and treatment effectiveness of 90%. In this scenario, for a 55‐year‐old patient with moderate liver fibrosis (Metavir stage F2), the cost‐effectiveness of immediately initiating treatment at F2 (versus delaying treatment until F3) was $37, 300/QALY. For patients immediately treated at F0 (versus delaying treatment until F1), the threshold of treatment costs that yielded $50, 000/QALY and $100, 000/QALY cost‐effectiveness ratios were $22, 200 and $42, 400, respectively. Conclusion: Immediate treatment of HCV‐infected patients with moderate and advanced fibrosis appears to be cost‐effective, and immediate treatment of patients with minimal or no fibrosis can be cost‐effective as well, particularly when lower treatment costs are assumed. (Hepatology 2015;61:1860–1869)